2020
DOI: 10.1007/s40271-020-00484-x
|View full text |Cite
|
Sign up to set email alerts
|

Mobilising the Next Generation of Stated-Preference Studies: the Association of Access Device with Choice Behaviour and Data Quality

Abstract: for their feedback during the development of the stated preference survey. Data availability:The datasets generated during and/or analysed during the current study are still undergoing further analyses and are unavailable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
1
5
1
Order By: Relevance
“…Using a mobile phone to complete the survey reduced error variance which could be explained by people on a smartphone adopting heuristics decision‐making. This finding, however, contradicts a recent study that found that choice behaviors (i.e., taste and scale heterogeneity) were not driven by the access device (desktop or mobile phone) (Vass & Boeri, 2021). Future research should investigate this issue further.…”
Section: Discussioncontrasting
confidence: 93%
“…Using a mobile phone to complete the survey reduced error variance which could be explained by people on a smartphone adopting heuristics decision‐making. This finding, however, contradicts a recent study that found that choice behaviors (i.e., taste and scale heterogeneity) were not driven by the access device (desktop or mobile phone) (Vass & Boeri, 2021). Future research should investigate this issue further.…”
Section: Discussioncontrasting
confidence: 93%
“…Mobile or tablet users tend to spend about 8-9% longer in completing a choice task. This result is in line with previous research (Couper & Peterson, 2016;Liebe et al, 2015;Vass & Boeri, 2021;Wells et al, 2013) and suggests that comparing alternatives might be more difficult when using devices with smaller screen size. In addition, there are two possible explanations hypothesized by Gummer and Rossman (2015): first, the speed of the Internet connection might be slower for smartphones and tablets; and second, this type of devices is used outside home more often than computers, implying that these users may be subject to more distractions and interruptions during the survey.…”
Section: Rt At the Choice-task Levelsupporting
confidence: 92%
“…Notably, while respondents were recruited via a reputable marketing firm of panel providers, careful quotas were imposed to ensure representativeness. Nevertheless, whether the sample of panel members reflects the general population remains unknown [ 39 ]; furthermore, the survey was administered online [ 40 ], potentially resulting in a sample more intrinsically motivated in AMR than the wider public. Furthermore, respondents received detailed information about AMR during the survey to help provide the context for the choice scenarios presented in the DCE.…”
Section: Discussionmentioning
confidence: 99%